THE NEW CLASSIFICATION OF DISTAL EXTRAHEPATIC CHOLANGIOCARCINOMA-MORPHOLOGICAL ANALYSIS AND REVIEW OF LITERATURE - Spasevska, Liljana; Dukova, B; Janevski, V; Shumkovski, A; Jankulovski, N (MACEDONIAN ASSOCIATION OF ANATOMISTS AND MORPHOLOGISTS, 2011)
Extrahepatic cholangiocarcinoma (EH-CCa) is a malignant tumor that arises from the ductal epithelium of the extrahepatic bile duct and it has been divided into perihilar and distal at the level of the cystic duct . As relatively rare disease perihilar and distal extrahepatic cholangiocarcinoma should be viewed as independent entities because of their distinct biology and management. The aim of the study was to make morphologic analysis of archive material of diagnosed EH-CCa at the Institute of pathology, Medical Faculty, Skopje in 5-year period and revision of the cases according to 7th edition (AJCC/UICC) TNM staging classification. We used archive material from the data base of the Institute of pathology, Medical Faculty, Skopje, for 7 cases diagnosed as distal EH-CCA between year 2006 and year 2010. Four analyzed adenocarcinomas showed periductal-infiltrating pattern of growth and 3 cases had massforming characteristics. One case revealed pancreatic involvement, 5 infiltrated the periductal soft tissue and 1 was confined to the ductal wall. In 3 cases peri/intraneural invasion was found and 2 cases had vascular tumor embolusses. There were 2 lymph nodes with metastases from 10 examined in only one case, in two cases there was no surgical resection of lymph nodes, and the rest cases were free from metastatic disease. Positive surgical margines we found in 2 cases and 2 were negative. The most of EH-CCA were diagnosed in stage IB, one was in stage IA and one in stage IIB. The purpose of 7th edition AJCC/UICC TNM staging system is predominantly prognostic and will require additional validation.
Keywords: extrahepatic cholangiocarcinoma; distal bile duct carcinoma; staging